The effectiveness of dual regulation and synergistic governance of market-incentivized carbon reduction policies and public environmental supervision: a study based on the sustainable development performance of listed companies in China - Chen, Jiahe; Yu, Wenhao (Frontiers in Environmental Economics, 2024)
Introduction In the current background of global economic slowdown, the traditional reliance on one regulatory instrument or the unilateral consideration of the effectiveness of one regulatory policy in policy formulation is no longer sufficient to cope with the increasingly complex contradictions between environmental protection and economic development. In the construction of a modernized environmental governance system, it has become an inevitable choice to achieve synergy between various environmental regulations. In China, the citizens' environmental supervision campaign that gradually emerged in 2006 and the local carbon trading pilots that started in 2013, as typical representatives of informal and formal environmental regulation respectively, provide vivid and realistic materials for our study. Methods Using econometric models and microdata from listed Chinese firms from 2009 to 2020, we analyze the profound logic and internal mechanism by which this synergistic governance effect of environmental regulation affects the economic society and the development pattern of firms. Results and discussion The study found that: (1) the synergistic effect of the carbon trading policy and citizens' environmental supervision can significantly promote the transition of enterprises to a sustainable development model, especially paying attention to the role of citizens' environmental supervision in this process. (2) The regional development level, cost transfer capability, and political connection can make the synergy of the two environmental regulations vary across firms. (3) The synergistic effect of environmental regulation promotes the behavior of enterprises in line with the requirements of sustainable development by influencing enterprises' R&D and innovation investment, resource allocation efficiency, and sustainable development awareness. (4) A favorable regional rule of law environment and moderate media attention can effectively increase the intensity of citizens' environmental supervision, and at the same time strengthen the effectiveness of synergistic governance of environmental regulation in the transformation and development of enterprises.